A Phylogenomic Perspective on Evolution and Discordance in the Alpine-Arctic Plant Clade Micranthes (Saxifragaceae) - Stubbs, Rebecca L.; Folk, Ryan A.; Xiang, Chun-Lei; Chen, Shichao; Soltis, Douglas E.; Cellinese, Nico (Frontiers in Plant Science, 2020)
The increased availability of large phylogenomic datasets is often accompanied by difficulties in disentangling and harnessing the data. These difficulties may be enhanced for species resulting from reticulate evolution and/or rapid radiations producing large-scale discordance. As a result, there is a need for methods to investigate discordance, and in turn, use this conflict to inform and aid in downstream analyses. Therefore, we drew upon multiple analytical tools to investigate the evolution of Micranthes (Saxifragaceae), a clade of primarily Arctic-alpine herbs impacted by reticulate and rapid radiations. To elucidate the evolution of Micranthes we sought near-complete taxon sampling with multiple accessions per species and assembled extensive nuclear (518 putatively single copy loci) and plastid (95 loci) datasets. In addition to a robust phylogeny for Micranthes, this research shows that genetic discordance presents a valuable opportunity to develop hypotheses about its underlying causes, such as hybridization, polyploidization, and range shifts. Specifically, we present a multi-step approach that incorporates multiple checks points for paralogy, including reciprocally blasting targeted genes against transcriptomes, running paralogy checks during the assembly step, and grouping genes into gene families to look for duplications. We demonstrate that a thorough assessment of discordance can be a source of evidence for evolutionary processes that were not adequately captured by a bifurcating tree model, and helped to clarify processes that have structured the evolution of Micranthes.